Coronavirus Disease 2019–Related Stigma in China: A Descriptive Study - Zhao, Li; Wang, Zhen; Guan, Jian; Shen, Panyan; Zhao, Wen; Zuo, Guoguo (Frontiers in Psychology, 2021)
COVID-19 tremendously impacts the physical and mental health of humans worldwide. Consequently, studies on COVID-19 remain extensive. However, most of them were mainly focused on the pathological mechanisms and treatment methods from medical perspectives. Various reports have indicated that COVID-19 is closely related to stigma and discrimination, but little statistical information has been integrated to describe the situation in China quantitively. Thus, this study investigated individuals’ COVID-19-related stigma. We collected online survey data from 1,920 Chinese participants from October to December 2020. Findings showed that 306 (15.94%), 285 (14.84%), 265 (13.80%), and 100 (5.21%) participants endorsed stigma toward individuals in high-risk areas, recovered COVID-19 patients, families of recovered COVID-19 patients, and frontline healthcare providers, respectively. To understand the possible factors that could impact the COVID-19-related stigma, knowledge about COVID-19 was investigated. Generally, knowledge about COVID-19 was negatively associated with COVID-19-related stigma in general, while no significant relationship existed between the knowledge about COVID-19 and COVID-19-related stigma in the groups who had held COVID-19-related stigma. Ultimately, individuals showed COVID-19-related stigma toward recovered patients and their families, individuals in high-risk areas, and frontline healthcare providers to some extent. Results of this study can provide reference to nations, governments, and organizations in addressing the stigma issues raised by the COVID-19 pandemic.